The effects of salt and storage temperature on microbiological changes in hot-smoked mirror carp (Cyprinus carpio L.) - Duman, Muhsine; Patir, Bahri; Duman, Erdal; Ilhak, O. Irfan (Asian Network for Scientific Information, 2007)
In this study, microbiological changes during processing and preservation of smoked mirror carp (Cyprinus carpio L.) fillets were examined. In the processing phase the brining in two different salt concentration and smoke were used. The conservation is realized in two different ambient temperatures. Starting from raw material, aw and pH levels as well as mesophilic, psychrophilic, staphylococcus-micrococcus, coliform, the yeast and mould counts were determined at every stage. In conclusion, the period preservation of smoked mirror carp fillets was dependent on salt concentration and preservation temperature. © 2007 Asian Network for Scientific Information.
Keywords: Hot smoked; Microbiological quality; Mirror carp (Cyprinus carpio)